问题 解答题
解方程
9x-3=
3
8

5
6
+
1
5
=
4
5

2
3
x+
1
6
x=
1
2

3
7
÷x×
1
3
=
5
14
答案

(1)9x-3=

3
8

9x-3+3=

3
8
+3,

9x=

27
8

9x÷9=

27
8
÷9,

x=

27
8
×
1
9

x=

3
8

(2)x÷

5
6
+
1
5
=
4
5

5
6
+
1
5
-
1
5
=
4
5
-
1
5

5
6
=
3
5

5
6
×
5
6
=
3
5
×
5
6

x=

1
2

(3)

2
3
x+
1
6
x=
1
2

2
3
+
1
6
)x=
1
2

5
6
x=
1
2

5
6
5
6
=
1
2
÷
5
6

x=

1
2
×
6
5

x=

3
5

(4)

3
7
÷x×
1
3
=
5
14

3
7
÷x×
1
3
×3=
5
14
×3,

3
7
÷x=
15
14

3
7
÷x×x=
15
14
×x,

15
14
×x=
3
7

15
14
×x÷
15
14
=
3
7
÷
15
14

x=

3
7
×
14
15

x=

2
5

单项选择题
单项选择题